El naturalismo trascendental del último wittgenstein (1996)
The present article considers an interiía! tensión in Wittgenstein's late philosophy. In what 1 cali his 'naturalism', Wittgenstein circumscribes  philosophical reflection to natural objects, to «making natural history». n his 'transcendentalism', he focuses on the «possibility of phenomena»  and distinguishes philosophical method from the method ofthe natural  " sciences. I show that his'transcendentalism'is present in his discussion :. ofrules and prívate language, arguing for an interpretation in terms oía  kantian type of transcendental synthesis. But far from contradicting his 'naturalism', both tendencies are inseparable and essential to the main purpose of his Philosophical Investigations.